Cone-beam CT angiography to assess the microvascular anatomy of intracranial arterial dissections. Issue 4 (August 2022) - Diana, Francesco; Raz, Eytan; Biraschi, Francesco; Romano, Daniele G; Toccaceli, Giada; Shapiro, Maksim; Peschillo, Simone
Background: Intracranial artery dissection is a rare and generally under-recognized cause of ischaemic stroke or subarachnoid haemorrhage. Objectives: The aim of this study was to analyse the efficacy of cone-beam computed tomography angiography (CBCT-A) to detect arterial ultrastructural alterations in intracranial artery dissection. Method: This is an observational and retrospective case series. Results: Between January 2018 and November 2020, four patients were admitted with an acute ischaemic stroke due to intracranial dissection studied with CBCT-A. In all cases, the CBCT-A documented vascular ultrastructural alterations related with the intracranial dissection. Conclusions: CBCT-A is an intraprocedural diagnostic technique that is useful for the diagnosis of intracranial dissections.